Implementation of Al-Miftah Lil Al-'Ulum Program in Learning to Read Kitab Kuning at Pondok Pesantren Nurul Huda - Hufron, A; Wahid, Abdul (Maharot : Journal of Islamic Education, 2023)
The al-Miftah lil 'Ulum program is a special program or selected group at pondok pesantren Nurul Huda, Pakamban Laok, Pragaan, Sumenep. The purpose of the al miftah program can improve the ability to read kitab kuning of students. This type of research is a qualitative case study whose data collection process is by observation, documentation, and interviews. While the data analysis is interactive analysis by reducing the data, displaying and verifying it then making conclusions. In this study using descriptive qualitative method. Based on the results of observations of teaching teachers and students, it is known that by participating in the al-Miftah lil 'Ulum Program at pondok pesantren Nurul Huda, the ability to read kitab kuning of students increases. From the results of the study, it was concluded that the al-Miftah lil 'Ulum Program was effective and efficient to be implemented at pondok pesantren Nurul Huda, Pakamban Laok, Pragaan, Sumenep in learning kitab kuning.